Managing ecological disturbances: Learning and the structure of social-ecological networks. (November 2018) - Baggio, J.A.; Hillis, V.
Abstract: Ecological disturbances (i.e. pests, fires, floods, biological invasions, etc.) are a critical challenge for natural resource managers. Land managers play a key role in altering the rate and extent of disturbance propagation. Ecological disturbances propagate across the landscape, while management strategies propagate across social networks of managers. Here we use an agent-based model to examine the joint diffusion of ecological disturbances and management strategies across a social-ecological network, accounting for the fundamental role of social-ecological feedbacks. We examine the management of a generic ecological disturbance as a function of different learning strategies and the social-ecological network. Our approach provides a general scaffold that can be modified to examine a variety of processes in which both social and ecological flows propagate across a social-ecological network. Our findings highlight the importance of full and accurate information to assess successful strategy, limited clustering and alignment between the social and the ecological system. Highlights: We present a generic model to assess how learning and ecological disturbances interact on a social-ecological network. Generic ecological disturbances (i.e. fires, floods, biological invasions etc.) propagate on an ecological network and treatment adoption depends on the interacting social-ecological network. Ecological disturbances affect the utility of land managers. Land managers can treat ecological disturbances at a cost, and their decision to treat depends on the effect of the ecological disturbance, and how people adopt and learn (success or conformist bias imitation, and/or individual learning). Results indicate that full, accurate information, coupled with success bias imitation, reduced local clustering, connectivity in the social-ecological network and alignment between the social and the ecological layer of the network are key to reduce the prevalence of ecological disturbances.